Dampak Perkembangan Teknologi Berbasis Data Terhadap Manajemen Operasional Distribusi Air Minum Dalam Kemasan - Febrian, Arya Lintar; Dewanti, Mentari Clara (Universitas YPPI Rembang, 2025)
CV Mekar Jaya Sentosa is a company engaged in the distribution of bottled drinking water (AMDK) in Central Java, utilizing statistical software as a system for data processing. The company faces challenges in managing the distribution of AMDK amidst rapid technological advancements. In this era of globalization, electronic information is more accessible than ever, providing efficiency in time management, ease of data processing, and necessary monitoring capabilities. Despite these advantages, there remains a gap in data management that hinders the formulation of more effective operational strategies.This journal aims to inform startup business owners on how to manage data-driven businesses by detailing methods for data processing and the necessary visualizations tailored to their business needs, as well as strategies that are more responsive to consumer satisfaction. Through the case study of CV Mekar Jaya Sentosa, insights will be gained on effective visualization techniques and the processes involved in running a data-centric business.The research findings indicate that data analysis can identify various market segments, consumer preferences, and the potential strengths of product distribution in specific regions. The proposed distribution strategies based on these analyses are expected to enhance the effectiveness of product distribution and improve consumer satisfaction with the offerings.